Giúp mk với cảm ơn nhìu

Question

Giúp mk với cảm ơn nhìu
giup-mk-voi-cam-on-nhiu

in progress 0
Khánh Gia 1 year 2020-10-13T19:20:26+00:00 1 Answers 96 views 0

Answers ( )

    0
    2020-10-13T19:21:37+00:00

    $g$) $(x-2)^{2x+3} = (x-2)^{2x+1}$

    $⇔ (x-2)^{2x+3} – (x-2)^{2x+1} = 0$

    $⇔ (x-2)^{2x+1} . [(x-2)^{2} – 1] = 0$

    $⇒$  \(\left[ \begin{array}{l}x=2\\x=3\\x=1\end{array} \right.\) 

      Vậy $x$ $∈$ `{1;2;3}`.

    $h$) $x^2 + 2x = 0$

    $⇔ x(x+2) =0$

    $⇒$ \(\left[ \begin{array}{l}x=-2\\x=0\end{array} \right.\) 

     Vậy $x$ $∈$ `{-2;0}`.

    $i$) $(x^4 + 0,0001)(x+1995)=0$

    $⇒$ \(\left[ \begin{array}{l}x^4=-0,0001(KTM)\\x=-1995\end{array} \right.\) 

      Vậy $x=-1995$.

    $k$) $(x-2) + 3x^2 – 6x = 0$

    $⇔ (x-2) + 3x(x-2) = 0$

    $⇔ (1+3x)(x-2) = 0$

    $⇒$ \(\left[ \begin{array}{l}x=\dfrac{-1}{3}\\x=2\end{array} \right.\) 

       Vậy $x$ $∈$ `{-1/3;2}`.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )